1998
DOI: 10.1091/mbc.9.9.2655
|View full text |Cite
|
Sign up to set email alerts
|

Tubulin Polyglycylation: Differential Posttranslational Modification of Dynamic Cytoplasmic and Stable Axonemal Microtubules inParamecium

Abstract: Polyglycylation, a posttranslational modification of tubulin, was discovered in the highly stable axonemal microtubules of Paramecium cilia where it involves the lateral linkage of up to 34 glycine units per tubulin subunit. The observation of this type of posttranslational modification mainly in axonemes raises the question as to its relationship with axonemal organization and with microtubule stability. This led us to investigate the glycylation status of cytoplasmic microtubules that correspond to the dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 52 publications
3
55
0
Order By: Relevance
“…The reversible nature of polyglycylation and the existence of tubulin deglycylases were previously shown in cytoplasmic extracts of the ciliate Paramecium tetraurelia, but the enzymes were not identified (6). gDIP1 and gDIP2 belong to the MH clan, subfamily M20C.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The reversible nature of polyglycylation and the existence of tubulin deglycylases were previously shown in cytoplasmic extracts of the ciliate Paramecium tetraurelia, but the enzymes were not identified (6). gDIP1 and gDIP2 belong to the MH clan, subfamily M20C.…”
Section: Discussionmentioning
confidence: 94%
“…We demonstrated that the g14-3-3 is modified in a peculiar fashion by the phosphorylation of Thr-214 and the polyglycylation of Glu-246 (3,4). The glycylation, first discovered at the C-terminal domain of ␣-and ␤-tubulin, is a post-translational modification consisting of the covalent addition of one or multiple glycines to the ␥-carboxyl groups of specific glutamic acids of target proteins (6,7). Recently, polyglycylation has been also reported for several proteins, including the mammalian nucleosome assembly proteins (8 -10).…”
mentioning
confidence: 97%
“…The GT335 MAb recognizes a branch point of a glutamyl side chain consisting of at least one glutamate on either ␣-or ␤-tubulin (63) (see the footnote to Table S1 in the VOL. 7,2008 TTLL1 AND TTLL9 GLUTAMYLATE ␣-TUBULIN 1363 supplemental material). GT335 labeled all of the microtubule locations in vegetative cells ( Fig.…”
Section: Subtypes Of Microtubules Inmentioning
confidence: 99%
“…7,2008 TTLL1 AND TTLL9 GLUTAMYLATE ␣-TUBULINTetrahymena strain, ATU1-6D, in which all six glutamates within the CTT of Atu1p (the only conventional ␣-tubulin in Tetrahymena) (38) were replaced with aspartates to preserve the charge but prevent polymodifications. The ATU1-6D cells are viable and motile, indicating that polymodifications on ␣-tubulin are not essential.…”
Section: Subtypes Of Microtubules Inmentioning
confidence: 99%
See 1 more Smart Citation